Parents living with a child afflicted by a life-limiting medical condition: Typology of their narrative identity - Sylvie Lafrenaye; Marc Dumas; Émilie Gosselin; André Duhamel; Patricia Bourgault (Qualitative Research in Medicine & Healthcare)
Parents of children suffering from a life-limiting medical condition struggle with difficult existential questions. Our objective was to understand why those parents’ interactions with the medical world were so different, ranging from hostile to collaborative, with the themes of identity, spirituality and serenity. A grounded theory design based on the narrative identity framework was used to interview sixteen parents. Three categories emerged: i) Parents in the Almighty category delegate all their power to God or medicine and are the most suffering parents as they do not author their life; ii) Parents in the Me category make every decision on their own causing much anxiety, and they become rebarbative to the medical world; iii) Parents in the Guide category take advice from others, while remaining the authors of their stories and are the most serene parents. Understanding and recognizing these categories can have a major impact on communication with those families.